Different intensities of aerobic training for patients with type 2 diabetes mellitus and knee osteoarthritis: a randomized controlled trial - Su, Chi; Huang, Lihua; Tu, Shaochen; Lu, Shengdi (Frontiers in Endocrinology, 2024)
Objective The purpose of this study was to compare different intensities of aerobic exercise for patients with knee osteoarthritis (KOA) and type 2 diabetes mellitus (T2DM) in terms of glycemic control, pain relief, and functional outcomes. Methods A prospective randomized open-label parallel multicenter clinical trial conducted at two hospitals in Shanghai and Sichuan that included 228 patients with type 2 diabetes mellitus (T2DM) and knee osteoarthritis (KOA). Enrollment occurred between January 2021 and February 2023, and follow-up was completed in September 2023. Participants were randomized to threshold training/high-intensive stationary cycling training (n=76), intensive endurance/moderate-intensive stationary cycling training (n=77), and regular rehabilitation programs (n=75). The primary outcome at the 6-month follow-up was the HbA1c level. Key secondary outcomes included the Knee Injury and Osteoarthritis Outcome Score (KOOS) subscale of pain and quality of life. Results Of 228 patients, 212 (93%) completed the trial. The mean adjusted (sex, baseline BMI, and baseline outcome measures) HbA1c level at the 6-month follow-up decreased significantly in the high-intensive training group compared with other groups (high-intensity group vs. control group; difference, 0.51%, 95% confidence interval, 0.05% to 1.15%). Mean KOOS subscales of pain and quality of life were statistically significantly different between the control group and moderate-intensity or high-intensity groups, but no statistical differences were noted between the different intensities of aerobic exercise. Patients in all groups achieved a greater reduction in BMI but no significant differences were observed between groups. Conclusion In KOA and T2DM patients, high-intensity stationary cycling can significantly improve glycemic control compared with moderate-intensity and regular rehabilitation programs. However, high-intensity stationary cycling does not exert a superior effect on pain relief and functional improvement for KOA compared with moderate-intensity and regular rehabilitation programs.